Research advances in the association between peripheral blood monocyte to high-density lipoprotein cholesterol ratio and acute cerebral infarction - HAO Chenyu, LUAN Huiwen, CHEN Xuecong, ZHANG Bin, TIAN Yuhe, SHI Baolin (精准医学杂志)
Acute cerebral infarction is one of the most important diseases that endanger the life and health of citizens. Inflammatory response is closely associated with the development and progression of acute cerebral infarction, and the levels of inflammatory markers can reflect the severity of inflammation. In recent years, monocyte to high-density lipoprotein cholesterol ratio (MHR) has attracted wide attention as a newly applied indicator for the degree of inflammatory response. This article reviews the association between peripheral blood MHR and acute cerebral infarction in terms of high-risk factors, risk prediction, early functional deterioration, severity assessment, hemorrhagic transformation, and prognosis.